The Development of Interactive Learning Multimedia for Zakat Lesson - Hakim, Mukhammad Luqman (EDUKASIA, 2020)
This research aims to produce multimedia learning and provide understanding to students of the importance of paying zakat in accordance with applicable regulations. The research subjects are 33 students of class VII.I at SMPN 7 Kediri. This study uses research and development method of Lee and Owen’s model. The procedures in research and development are needs analysis, design, development, implementation and evaluation. The data analysis uses a closed questionnaire with a Likert scale. This research and development received positive responses from experts and stated that interactive learning multimedia was feasible to use and did not require revision. A whole responses from students stated that this learning multimedia provides a new learning experience and fosters a sense of awareness of the importance and benefits of paying zakat.